At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Mg(OH)2+2 HCI = MgCI2+ H2O

Sagot :

Answer:

Mg(OH)2 + 2HCI ⇒ MgCI2 + 2H2O

Explanation:

In order to balance a chemical equation you need to make sure both sides of the equations are equal.

Mg(OH)2 + 2HCI = MgCI2 + H2O

Mg = 1

Oh = 2

HCI = 2

Products:

Mg = 1

CI = 2

H = 2

O = 1

2H20 = 1 × 2 = 2

2 × 2 = 4

2HCI

1 × 2 = 2

Mg(OH)2 + 2HCI ⇒ MgCI2 + 2H2O

Hope this helps.